Steel tide - Parker, Natalie C. (Parker, Natalie C. Seafire trilogy, 2020)
Rescued by the Blades, a nomadic crew hiding from Aric Athair, Caledonia seeks their help to find the Mors Navis and her sisters, defeat Aric's fleet, and take back the Bullet seas.